Low cost ergonomics improvement in small and medium enterprise (SME) - Maziani Musa (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
The objectives of this study are to identify the common ergonomics issues or problems in Small and Medium Enterprise (SME) and to implement low-cost ergonomics improvement for SME based on selected company. This study was implemented to 7 workers in the industry that produced fish sausages (keropok lekor) at Sinku Food Industries Sdn Bhd.